The Concept of Belief in Religions: A Study from the Psychological and Human Behaviourial Perspectives - Mat Akhir, Noor Shakirah (SOSIOHUMANIKA, 2011)
ABSTRACT: This paper is of utmost significance as it attempts to discuss the concept of belief in religions with special reference to Islam. Among the leading factors that have influence on ones belief are ethnic, race, lineage, nationality, emotion, and knowledge. In addition, this paper discusses the impact of belief on human psychology and behaviour. Faith and belief based on religion will have great influence on human psychology and behaviour, and thus shaping oneâs personality. There are differences between the concept of belief based on religion and that of ideology. In this respect, Al-Shahrastani (469-548 AH / 1076-1153 AD), in his magnum opus of Kitab al-Milal wa al-Nihal, distinguishes religious beliefs from other beliefs which are based on ideology and human philosophical thought. On another note, psychological values are the key aspect of oneâs religious belief. The psychological impacts on ones belief among others are tranquility, balanced soul, strong personality, and spiritual strength. In short, the psychological impacts have the ability to shape the behaviour of one who believes in religion. Understanding this concept is vital, especially in the society with multi-racial and multi-belief.Â  Key words: Concept of faith, psychological aspect, human behaviour, religion and ideology, and strong personality and spiritual strength.About the Author: Assoc. Prof. Dr. Noor Shakirah Mat Akhir is a Senior Lecturer at the School of Humanities USM (Science University of Malaysia), USM Campus, Minden 11800, Pulau Pinang, Malaysia. She can be reached at: shakirah@usm.myHow to cite this article? Mat Akhir, Noor Shakirah. (2011). âThe Concept of Belief in Religions: A Study from the Psychological and Human Behaviourial Perspectivesâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.4, No.2 [November], pp.249-258. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (September 17, 2011); Revised (October 19, 2011); and Published (November 20, 2011). Â  Â